A MULTISECTORAL STRATEGY TO OVERCOME POVERTY AND STUNTING THROUGH SOCIAL AND ECONOMIC EMPOWERMENT IN BABAKAN MADANG VILLAGE BOGOR WEST JAVA - Rendra Fahrurrozie; Kholid Koyubi; Widya Aristiana; Taufiq Kamal; Nurhayati (STAI Sirojul Falah Bogor, 2025)
This study examines the effectiveness of social and economic programmes in reducing poverty and stunting through a qualitative approach with flow chart analysis. The study was conducted in two posyandu where intervention programmes were implemented, including nutrition counselling, vitamin A distribution, and economic empowerment programmes based on local food production. The results showed a decrease in the prevalence of stunting and an increase in community awareness of the importance of a healthy diet and community-based economic strengthening. The main factors supporting the success of this programme include active community participation, support from village officials, and optimisation of local resources. However, some constraints remain, particularly in terms of information dissemination and limited access to additional resources. The implications of these findings confirm that a community-based approach that integrates social, economic and health aspects is highly effective in improving community welfare. Recommendations include strengthening institutional capacity, utilising technology in health education, and diversifying local food-based economic empowerment strategies. In addition, further research is needed to evaluate the long-term impact and potential replication of the programme in various regions with different socio-economic characteristics. The results of this study are expected to serve as a foundation for policy development based on openness and sustainability in an effort to accelerate poverty and stunting reduction.